Intracellular Trafficking and Subcellular Distribution of a Large Array of HPMA Copolymers - Callahan, Jon (2009)
The basic physicochemical properties that determine the distribution and fate of synthetic macromolecules in living cells were characterized using fluorescently labeled HPMA (N-(2-hydroxypropyl)methacrylamide) copolymers. Twelve different classes of water-soluble copolymers were created by incorporating eight different functionalized comonomers. These comonomers possessed functional groups with positive or negative charges or contained short hydrophobic peptides. The copolymers were fractionated to create parallel “ladders” consisting of 10 fractions of narrow polydispersity with molecular weights ranging from 10 to 200 kDa. The intracellular distributions were characterized for copolymer solutions microinjected into the cytoplasm of cultured ovarian carcinoma cells. Even the highest molecular weight HPMA copolymers were shown to quickly and evenly diffuse throughout the cytoplasm and remain excluded from membrane-bound organelles, regardless of composition. The exceptions were the strongly cationic copolymers, which demonstrated a pronounced localization to microtubules. For all copolymers, nuclear entry was consistent with passive transport through the nuclear pore complex (NPC). Nuclear uptake was shown to be largely dictated by the molecular weight of the copolymers, however, detailed kinetic analyses showed that nuclear import rates were moderately, but significantly, affected by differences in comonomer composition. HPMA copolymers containing amide-terminated phenylalanine-glycine (FG) sequences, analogous to those found in the NPC channel protein, demonstrated a potential to regulate import to the nuclear compartment. Kinetic analyses showed that 15 kDa copolymers containing GGFG, but not those containing GGLFG, peptide pendant groups altered the size-exclusion characteristics of NPC-mediated nuclear import.